2013
DOI: 10.1186/1869-5760-3-21
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic retinal vasculitis, arteriolar macroaneurysms and neuroretinitis: clinical course and treatment

Abstract: BackgroundThe purpose of the study is to describe the clinical course and treatment of idiopathic retinitis, vasculitis, aneurysms and neuroretinitis. The study utilized non-randomized, retrospective and interventional case series. The eight eyes of six patients were analysed. Testing included wide fluorescein angiography, indocyanine green angiography and systemic evaluation. Treatment involved observation, panretinal laser photocoagulation (PRP) for peripheral retinal ischemia, grid laser for macular oedema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…This is similar to a study on IRVAN cases which suggested using laser photocoagulation in eyes with retinal ischaemia even before NV is formed when there is more than two quadrants affected with capillary non-perfusion. 20 In our cohort, the use of corticosteroids was associated with a reduced risk of vision loss, including eyes with IRV and non-IRV. The use of corticosteroids and other antiinflammatory medications in managing vasculitis and some of its associated complications, such as CME, contributes to their role in preventing vision loss 19 .…”
Section: Characteristics Of the Retinal Ischemia Among The Studied Groupmentioning
confidence: 59%
“…This is similar to a study on IRVAN cases which suggested using laser photocoagulation in eyes with retinal ischaemia even before NV is formed when there is more than two quadrants affected with capillary non-perfusion. 20 In our cohort, the use of corticosteroids was associated with a reduced risk of vision loss, including eyes with IRV and non-IRV. The use of corticosteroids and other antiinflammatory medications in managing vasculitis and some of its associated complications, such as CME, contributes to their role in preventing vision loss 19 .…”
Section: Characteristics Of the Retinal Ischemia Among The Studied Groupmentioning
confidence: 59%
“…3 Favorable results have been noted with use of Ranibizumab. 6 Monoclonal antibodies such as Infliximab have been tried in treatment of IRVAN.…”
Section: 3mentioning
confidence: 99%
“…7 Duration of disease is variable and may take many months to years to manifest. 3 In our case presentation was acute and bilateral which prompted early initiation of treatment. Macular edema and exudates contributed to vision loss.…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations